2001
DOI: 10.1046/j.1365-2362.2001.00778.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bile salts and aliphatic ionic surfactants on human lymphocyte proliferation

Abstract: Amphiphilic negatively charged molecules inhibit T-cell proliferation to an extent that is dependent upon their hydrophobicity. These results may be explained, at least in part, by a modification in the cell membrane lipid bilayer structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…We found a significant negative correlation between the number of circulating DN T‐cells and the serum level of total bile acids in PBC patients ( r = −0.480, P < 0.001, Figure A). It has been reported that several serum bile acid levels were elevated in PBC, such as glycochenodeoxycholic acid, glycocholic acid and LCA, and bile salts can inhibit the cytokine production and proliferation of lymphocytes . The rank order for bile acid hydrophobicity is LCA > deoxycholic acid > chenodeoxycholic acid > UDCA .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found a significant negative correlation between the number of circulating DN T‐cells and the serum level of total bile acids in PBC patients ( r = −0.480, P < 0.001, Figure A). It has been reported that several serum bile acid levels were elevated in PBC, such as glycochenodeoxycholic acid, glycocholic acid and LCA, and bile salts can inhibit the cytokine production and proliferation of lymphocytes . The rank order for bile acid hydrophobicity is LCA > deoxycholic acid > chenodeoxycholic acid > UDCA .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that several serum bile acid levels were elevated in PBC, such as glycochenodeoxycholic acid, glycocholic acid and LCA, 25 and bile salts can inhibit the cytokine production and proliferation of lymphocytes. 26,27 The rank order for bile acid hydrophobicity is LCA > deoxycholic acid > chenodeoxycholic acid > UDCA. 28 We therefore co-cultured PBMC with LCA, sodium glycochenodeoxycholate, sodium glycocholate hydrate and Figure 6D).…”
Section: Lca Downregulated Perforin Expression In Dn T-cells and Inmentioning
confidence: 99%
“…Similar phenomena have been described with other micelle forming compounds. Podevin et al [33] described the effect of bile salts on lymphocyte proliferation by claiming that the biological effect was partly due to the modification of the structure of the cell membrane lipid bilayer by the surface activity and hydrophobicity of bile salts. Similarly, Sudo et al [34] described that succinolyl trehalose lipid-3 (STL-3) inhibited the growth of Human HL-60 cells at or near the CMC (4 μM).…”
Section: Discussionmentioning
confidence: 99%
“…Various hydrophobic compounds such as cholesterol, bile salts, and ionic surfactants have been previously shown to bind to and to change the composition of cellular membranes, causing changes in binding kinetics and related cellular consequences. 12,13 Compounds acting through further nonspecific modes might also be identified.…”
Section: Discussionmentioning
confidence: 99%